2014
DOI: 10.1186/1471-2334-14-217
|View full text |Cite
|
Sign up to set email alerts
|

Differences in outpatient care and treatment utilization for patients with HIV/HCV coinfection, HIV, and HCV monoinfection, a cross-sectional study

Abstract: BackgroundFew studies have explored how utilization of outpatient services differ for HIV/HCV coinfected patients compared to HIV or HCV monoinfected patients. The objectives of this study were to (1) compare annual outpatient clinic visit rates between coinfected and monoinfected patients, (2) to compare utilization of HIV and HCV therapies between coinfected and monoinfected patients, and (3) to identify factors associated with therapy utilization.MethodsData were from the 2005–2010 U.S. National Hospital Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…Used in combination with enhanced efforts to engage patients in care and shared health care models between regional specialized HCV clinics and primary care providers, there is great opportunity to increase treatment initiation and completion in this population. Overall, our results suggest that innovative approaches to HCV care for PWID should be considered, including involving peers in care, locating care in harm reduction environments, integration of HCV care with substance use and social service delivery, and use of telehealth services (Gonzalez et al, 2017;Johnson et al, 2014;Meyer et al, 2015;Talal, Thomas, Reynolds, & Khalsa, 2017;Tyndall, 2015).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Used in combination with enhanced efforts to engage patients in care and shared health care models between regional specialized HCV clinics and primary care providers, there is great opportunity to increase treatment initiation and completion in this population. Overall, our results suggest that innovative approaches to HCV care for PWID should be considered, including involving peers in care, locating care in harm reduction environments, integration of HCV care with substance use and social service delivery, and use of telehealth services (Gonzalez et al, 2017;Johnson et al, 2014;Meyer et al, 2015;Talal, Thomas, Reynolds, & Khalsa, 2017;Tyndall, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Our results are also consistent with other studies that have found low rates of treatment (Public Health Agency of Canada, 2013). People who use drugs face multiple barriers to care, including at the provider level (e.g., discrimination), system level (e.g., lack of drug insurance, lack of flexible clinic hours), and structural level (e.g., laws related to drug use); these barriers also interact in dynamic ways within specific contexts (Grebely et al, 2013b;Johnson, Toliver, Mao, & Oramasionwu, 2014;Wagner et al, 2009;Wolfe et al, 2015). Patient-related barriers, such as frequent injecting of drugs, may also be important, although evidence indicates that people who are actively using drugs can also be highly treatment adherent (Gonzalez, Fierer, & Talal, 2017;Grebely et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Caring for patients who use illicit drugs presents challenges to the health care team that require patience, experience, and an understanding of the dynamics of substance use and addiction. Nonetheless, programs are successfully integrating hepatitis C care for IV drug users into health-care settings [29]. Patient-level barriers include non-adherence to medical care, refusal of therapy, and social circumstances [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Additional measures will evaluate linkage to care by measuring the proportion of patients who initiated HIV care or HCV care before the 3-month follow-up among those whose test results were positive for HIV and/or HCV. Linkage to care for HIV or HCV will be measured separately, to account for variations in barriers to initiating care, which may be greater for HCV than barriers to initiating HIV medical care [ 67 ].…”
Section: Methodsmentioning
confidence: 99%